Massive, spontaneous ruptured renal subcapsular haematoma following thrombolytic therapy in acute st-elevation myocardial infarction / Raja Ezman Faridz Raja Shariff and Sazzli Shahlan Kasim. - Raja Shariff, Raja Ezman Faridz; Kasim, Sazzli Shahlan (Universiti Teknologi MARA Cawangan Selangor, 2019)
Thrombolytic therapy remains widely used in majority of developing countries, where delivery of primary percutaneous coronary intervention (PCI) remains a challenge. Unfortunately, complications following such therapy remains prominent, predominantly bleeding-related problems. We present a rare case of massive renal subcapsular haemorrhage and hematoma following thrombolytic therapy. A 61-year old gentleman presented following an episode of chest pain due to acute ST-elevation myocardial infarction. Due to potential delays in obtaining PCI, the patient was counselled for thrombolysis using streptokinase which he had consented to. Unfortunately, within 36 hours of admission, he developed abdominal pain, haematuria, hypotension and altered mental status, associated with acute drops in haemoglobin levels. Following initial resuscitation efforts, a Computed Tomography scan of the abdomen was performed revealing a massive renal subcapsular hematoma, likely secondary to previous thrombolysis. Renal subcapsular hematoma can either be spontaneous or iatrogenic, the latter often due to coexisting renal-based neoplasm or vasculitidies. Iatrogenic causes include trauma, following renal biopsies or anticoagulation therapy amongst a few others. Iatrogenic renal subcapsular haemorrhage and hematoma formation are rare following thrombolysis. Our literature search revealed only one other similar case, although this was following administration of recombinant Tissue Plasminogen Activator in a case of acute ischaemic cerebrovascular accident. This case highlights the complexity in management, following the findings in terms of need for cessation of dual antiplatelet therapy and timing for PCI and stent selection.